Soil organic carbon increase on conversion of native savanna to improved pasture in two regions of Colombia - Sandra Loaiza; Ciniro Costa Jr; Mayesse A. daSilva; Ngonidzashe Chirinda; Idupulapati Rao; Jacobo Arango; Jeimar Tapasco; Glenn Hyman (Grassland Research)
Abstract Background There is limited knowledge on how to increase soil organic carbon (SOC) stocks under tropical conditions. This study investigates SOC changes after converting land from native savanna (NS) to improved pasture (IP) land use. Methods Two acidic soil conversion sites were examined: (i) a poorly drained slope with medium‐texture soil (Casanare [CAS]1) and (ii) flat terrain with fine‐texture soil (CAS2). Another flat site was evaluated (Atlántico [ATL]), with fine‐textured to moderately textured neutral soil. Soil samples were collected and analyzed. SOC stocks (0–60 cm soil depth) were estimated, with a complex analysis of variance analyzing pasture type and soil depth. Results NS to IP conversion resulted in significant SOC accumulation in two regions, with losses in one (CAS2). ATL showed higher SOC accumulation than CAS. IP adoption led to SOC accumulation at depth (0–60 cm) after 10 years in CAS1. Elevated clay content in CAS2 favored SOC storage, while poorly drained areas hindered accumulation in CAS1. Cultivating rice before IP at CAS2 likely depleted SOC (0–20 cm), with 4 years of IP not restoring initial levels. Conclusions Adopting IP over NS can increase SOC. Grassland type, soil properties, and land‐use change all influence SOC accumulation. These data inform sustainable land management for low‐emission livestock production.